French visual dictionary - Prezelin, Maurane; Reid, Lauren; Thomas, Emma (Collins, 2019)
Immerse yourself in this photographic guide to the key words and phrases in French. This attractive pocket-sized is a perfect travel companion and provides a practical guide to French language and culture. Everyday words are arranged in themes with carefully selected up-to-date images to illustrate key words and phrases, and an English and French index help you to find words quickly as you learn. 3,000 essential words and phrases for modern life in France are at your fingertips with topics covering food and drink, home life, work and school, shopping, sport and leisure, transport, technology, and the environment. Great care has been given to represent modern French culture and enhance your experience of France and its people, including customs, celebrations, and festivals. Plus, download your free audio to hear native speakers pronounce the word for each image and get your pronunciation pitch perfect.